Clinical and epidemiological characteristics in older adults with a diagnosis of hip fracture in a hospital in Lima, Peru. - Rondón, Claudia N (2021)
OBJECTIVES: To determine the clinical and epidemiological characteristics in older adults with hip fracture in a hospital in Lima, Peru. METHOD: Case series type study carried out in the trauma department of the PNP Central Hospital “Luis N. Saenz” during the period 2015-2018. Medical records of patients diagnosed with hip fracture were reviewed. RESULTS: A total of medical records were included. A predominance was found in the female sex (54.3%) and in patients over 80 years old (45%). Most of these events occurred at home (81.4%). Intertrochanteric fractures were the most frequent (60%), especially on the right side (51.4%), osteosynthesis was the most used therapeutic option (62.1%). Pain (92%) and functional impotence (91.4%) were the characteristic clinical presentation of hip fractures, and arterial hypertension was the most common associated pathology (52.2%). CONCLUSIONS: Hip fracture primarily affects people over 80 years of age, especially women with high comorbidity. The highest percentage occurs as a result of falls produced at home, with pain on the affected side being the main manifestation. The most common type of fracture is intertrochanteric and the most used treatment is osteosynthesis.